2013
DOI: 10.1590/s1519-69842013000200013
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of periphytic algae in wetlands (Palm swamps, Cerrado), Brazil

Abstract: The distribution of periphytic algae communities depends on various factors such as type of substrate, level of disturbance, nutrient availability and light. According to the prediction that impacts of anthropogenic activity provide changes in environmental characteristics, making impacted Palm swamps related to environmental changes such as deforestation and higher loads of nutrients via allochthonous, the hypothesis tested was: impacted Palm swamps have higher richness, density, biomass and biovolume of epip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
0
9
0
7
Order By: Relevance
“…According to Murakami et al (2009), the diatom predominance is associated to its characteristic morphological and physiological of secrete mucilage which enable the attachment and adhesion to substrates. Besides, Dunck et al (2013) reported that this characteristic provides a competitive advantage in less favorable environmental conditions imposed by volume reduction and current. Similarly, in this study, we observed an increasing in algal density this group in the reservoirs in the dry periods probably due to the increased environmental stability during this period.…”
Section: Discussionmentioning
confidence: 99%
“…According to Murakami et al (2009), the diatom predominance is associated to its characteristic morphological and physiological of secrete mucilage which enable the attachment and adhesion to substrates. Besides, Dunck et al (2013) reported that this characteristic provides a competitive advantage in less favorable environmental conditions imposed by volume reduction and current. Similarly, in this study, we observed an increasing in algal density this group in the reservoirs in the dry periods probably due to the increased environmental stability during this period.…”
Section: Discussionmentioning
confidence: 99%
“…The most common group in terms of species richness, Zygnematophyceae, is known for its ecological preference for oligo-mesotrophic waters, with slightly low pH (Coesel & Meesters 2007). For this reason, these algae are frequently observed in Cerrado waters (Estrela et al 2011;Dunck et al 2013). Fonseca et al (2018) reported this group as the richest one among non-diatom periphytic algae in Cerrado wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…Shadow-adapted species such as Cocconeis and Gomphonema were reported as the most competitive among periphytic algae within harsh circumstances (e.g. light limitation) and were found to be well-developed in low-light environment in tropical wetlands (Dunck et al, 2013) and also under duckweed mats (Buczkó and Rajczy, 2001). Generally, tightly attached adnate/prostrate life forms live in the periphyton understory layer which enables them to avoid the shear stress and resist scour (Stevenson, 1996) and thus are found to be highly resistant forms in disturbed environments (Schneck and Melo, 2012).…”
Section: Figurementioning
confidence: 99%